Human Cell Transformation Role of Stem Cells and the Microenvironment - Rhim, Johng S.; Kremer, Richard (Advances in Experimental Medicine and Biology, 2012)
Rhim and Kremer's state-of-the-art volume on Human Cell Transformation: Role of Stem Cells and the Microenvironment highlights the latest findings on the current state of human cell transformation model systems and provides the insight into the molecular and cellular changes involved in the conversion of normal cells to neoplastic cells. Chapters cover all recently developed novel human cell models. In addition, the rapidly growing fields of knowledge regarding not only stem cells in cancer progression, but also the role of the microenvironments in human carcinogenesis are discussed. A wealth of topics is presented including: ·         Derivation of epithelial, fibroblastic, and hematopoietic in vitro model systems ·         Oncogenes ·         Tumor suppressor genes ·         Viral transformation ·         In vitro model systems for viral, chemical and radiation carcinogenesis ·         Cell aging ·         The multistep nature of human carcinogenesis ·         The role of stem cells and the microenvironment in tumorigenesis ·         The genes involved in multistep carcinogenesis Unique in both scope and focus - devoted solely to human cell transformation systems - Human Cell Transformation: Role of Stem Cells and the Microenvironment provides unparalleled, in-depth coverage for cancer researchers, cell and molecular biologists, hematologists, virologists, and workers in related fields. Essential reading for everyone who needs to be kept up-to-date in this fast-paced area!   Features Ø  Multistep models Ø  Breast cancer/Stem cells Ø  Prostate cancer/Stem cells Ø  Multistep / Genes.